Ecology and physiology of bacterial activity in a temperate saltmarsh lagoon, with an emphasis on nitrogen fixation - Tibbles, Brian Jonathan (Department of Biological Sciences, 2016)
Heterotrophic bacterial activity and nitrogen fixation are fundamental to nutrient regeneration and nitrogen cycling in saltmarsh ecosystems. Ecological and physiological aspects of bacterial production and nitrogenase activity in marine sediments and water were examined in Langebaan Lagoon, a temperate saltmarsh ecosystem. Emphasis was placed on factors modulating rates and patterns of nitrogen fixation. Nitrogen fixation appeared to be dominated by heterotrophic bacteria. Rates of nitrogen fixation (estimated by the acetylene reduction technique), and bacterial production (estimated by tritiated thymidine incorporation, Tri) were higher in fine, muddy sediments near the head of the lagoon (Geelbek) than in coarser, sandy sediments near the mouth of the lagoon (Oesterwal). These comparisons (between sites) reflected the higher bacterial abundance and organic content of sediments from Geelbek. Examinations of five sedimentary microhabitats at each site (including those associated with beds of the seagrass Zostera capensis, burrows of the sandprawn Callianassa kraussi at Oesterwal, and burrows of the mudprawn Upogebia africana at Geelbek) showed that bacterial activity was higher in surface sediments than in subsurface sediments. Highest rates of nitrogen fixation (annual mean, 0.28 + 0.07 nmol C2H4 g-1 dry sediment h-1) were measured in Zostera bed sediments at Geelbek. Thymidine incorporation activity and nitrogenase activity were higher in burrow linings than in adjacent subsurface sediments, suggesting that burrow linings provided an improved subsurface environment for bacterial activity. Burrow linings also had a higher organic content than subsurface sediments away from burrows. Nitrogenase activity was not detected in lagoon water.